Simptom-Simptom Trauma pada Anak Korban Kekerasan Seksual di Aceh - Zuliani, Hetti; Kee, Pau; Sapeer, Mohd Noor (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2024)
This study aims to identify and analyze trauma symptoms in child victims of sexual abuse in Aceh. Sexual violence against children is a serious issue that can cause long-term psychological impacts, significantly affecting their emotional and social development. Using a descriptive method, this research seeks to uncover the trauma symptoms in children who have experienced sexual abuse.The findings of this study indicate that child victims of sexual abuse in Aceh experience significant trauma symptoms, encompassing three main aspects: reexperience, avoidance, and hyperarousal. These symptoms not only impact the emotional condition of the children but also affect their behavior, social interactions, and future prospects. This study emphasizes the importance of appropriate and immediate intervention for child victims of sexual abuse, given the significant psychological impact. A comprehensive and sustainable approach is essential to ensure the emotional and social well-being of children who have been victims of sexual abuse, helping them build a better future